The Role Of Financial Literacy On MSMEs : A Qualitative Investigation - Benardi Benardi; Grace Yulianti; Ekawahyu Kasih; Farah Qalbia (Universitas 17 Agustus 1945 Semarang, 2023)
This study aims to investigate the significance of financial literacy in empowering Micro, Small, and Medium Enterprises (MSMEs). The research model adopts a qualitative approach to explore the nuanced factors affecting financial literacy among MSME owners and its impact on their businesses. A purposive sampling technique is employed to select participants from diverse MSME sectors. Data is collected through in-depth interviews and focus group discussions. The analysis utilizes thematic coding to identify patterns and themes within the qualitative data. The findings highlight the crucial role of financial literacy in enhancing the resilience and sustainability of MSMEs. Moreover, the study underscores the need for tailored financial education programs targeted at MSME owners to improve their financial management practices and foster business growth in a dynamic economic landscape.